Construction Safety Assessment Framework For Developing Countries: A Case Study Of Sri Lanka - Priyadarshani, Kanchana; Karunasena, Gayani; Jayasuriya, Sajani (Penerbit Universiti Sains Malaysia, 2013)
Construction safety on project sites is of utmost importance due to the nature of the construction industry. However, it is usually a secondary concern in a market-driven society where the main concern is completing projects at the required quality with minimum time and cost. Thus, safety issues are considered only after an accident occurs at a construction site with follow up measures to improve working conditions, especially in developing countries. In Sri Lanka, according to the International Labour Organisation, one out of six accidents and 25 out of 40 deaths occur at construction sites due to negligence or carelessness. These statistics show that safety is not adequately considered in the Sri Lankan construction industry. Therefore, proper safety management in construction is of utmost importance; hence, this study aims to introduce a benchmark to measure construction safety through a proposed safety management assessment framework. Factors affecting construction safety performance were explored through a questionnaire survey conducted in Sri Lanka. The results suggest that a benchmark of construction safety should be considered across six dominant groups of factors: management commitment, management measures, implementation, project nature, individual involvement and economic investment. Management commitment is the most dominant factor that affects construction safety and consists of implementing organisational safety policies, assigning safety responsibilities at all levels, etc. The proposed management framework will facilitate a benchmarking process and initiatives for improving construction safety performance in developing countries.